Blockchain-Oriented Software Development Issues: A Literature Review - AL-Ashmori, A. (Springer Science and Business Media Deutschland GmbH, 2021)
Blockchain-oriented software is a trend and a hot topic for discussion. The fitness of the common software engineering practices, tools, techniques, and methods for this new type of software has been discussed by many investigators. Furthermore, a new branch of software engineering known as blockchain-oriented software engineering has been announced as a new research field. However, the current issues of Blockchain-oriented software development have not been well defined yet. This study offers a systematic review procedure for software engineering, the stages pursued, the explanation of every one of them, along with its execution employed to the subject of the current issues in blockchain-oriented software development. The results of this study confirm that there 15 issues related to the exceptional properties of blockchain-oriented software affecting its development process. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.